GIÁ TRỊ ĐÓNG GÓP CỦA HỆ SINH THÁI RỪNG NHIỆT ĐỚI NAM CÁT TIÊN ĐỐI VỚI KHÍ HẬU THÔNG QUA GIÁM SÁT SỰ TRAO ĐỔI CỦA CÁC DÒNG NHIỆT LƯỢNG VÀ CO2 - Đinh, Bá Duy; V.C., Avilov; O.A., Kuricheva; J.A., Kurbatova; Lê, Xuân Sơn; Đào, Thị Thu Hường; Nguyễn, Thị Chinh; Trần, Thị Nhàn (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CONTRIBUTION VELUES OF NAM CAT TIEN TROPICAL FOREST TO CLIMATE THROUGH MONITORING THE EXCHANGES OF CO2 AND THERMAL ENERGY FLUXESMonitoring the exchanges of CO2 and energy between terrestrial ecosystems and the atmosphere is one of the approaches with high accuracy to quantify the contribution of tropical rainforest to climate. The results of the study in Nam Cat Tien forest ecosystem from 2012 to 2014 illustrate that this ecosystem plays the role of carbon sinks during 11 months in a years (over 90%) and the average uptake reaches 455,8 gC/m2 . In addition, about 74% of the net radiation (155,8 W/m2 ) that the ecosystem obtainsis transformed into latent heat and about 23% into sensible heat thanks to the ability to restrict surface flow, fix groundwater and remain moisture at the high level.